Digitalization of Romanian Education System: Is Romania Ready to Embrace Education 4.0? - Andreea-Cristina STROE (Informatică economică, 2022)
Due to the technological changes that have occurred in the last years, Education 4.0, a new educational paradigm has emerged. Romania, as any other country in the world, will face some challenges in order to adapt to the new educational context. Thus, the purpose of this paper is to provide an analysis of measures undertaken by our country in order to adapt to the changes. This paper relies on a theoretical study of the actions proposed by Romanian authorities. These actions will be analyzed in comparison with the regulations proposed by the European Union. Moreover, the study will focus on the degree of implementation of the actions and the perspectives our country has in order to meet the new global context. Overall, this paper contributes to the literature by placing Romanian education system in the new educational context brought to public attention by the Education 4.0 paradigm. In addition, it will find arguments in favor or against the alignment of our country with the new educational tends.